Karakteristik Analisis Wacana Kritis Dalam Wacana Berita “ Stebi Gelar Seminar Ekonomi Kreatif” - Melvin Arfiandita; Dessy Saputry; Amy Sabila (Teaching and Learning Journal of Mandalika (Teacher) e- ISSN 2721-9666, 2024)
Characteristics in Critical Discourse Analysis (AWK) include action, context, history, power, and ideology. When viewed from the news coverage of the Mina tragedy, it can be analyzed according to these five characteristics. The purpose of this study is to describe the characteristics of critical discourse analysis in the news discourse "STEBI Holds a Seminar on Creative Economy: Higher School of Business Economics holds a seminar on creative economy among university students. The data was collected using (a) the method of freeliving and proficient viewing, (b) note, (c) ) interviews, (d) literature study, and (e) documentation. The results of the research found based on these five characteristics, the most prominent are activities that can later generate jobs for the local community. In the news it was explained that students must have the enthusiasm to reach and pursue their desires and still have to study in order to increase knowledge so that what is the goal can be achieved. Keywords: critical discourse analysis, news discourse, Creative Economy Seminar